RANCANG BANGUN APLIKASI INTRUSSION DETECTION SYSTEM DENGAN MENGGUNAKAN METODE FUZZY - Nugroho, Indra Wahyu; Harianto, Harianto; Mardiana, I Dewa Gede Rai (Journal of Control and Network Systems, 2014)
As the development of networking technology, also emerging security isues such as Denial Of Service Attack (DoS). DoS is an attack used by hackers to shut down the computer system server so that the server can not provide service to the user. The first step to anticipate the variety of unwanted packets is to implement application intrussion Detection System (IDS) into a router. IDS application can be made by using the fuzzy method in which there are 3 stages of attack classification process that is establish variable membership functions, establish fuzzy rules and defuzzyfication. The first stage starts from storing data length and frequency into a fuzzy database table, furthermore search for alpha value of each rule and the last stage is to find the defuzzyfication value. From this value can be used to classify attacking level such as normal, low,medium and high. Result from this project IDS application can identify DoS attack which use some technic such as ICMP flooding, TCP flooding, UDP flooding and normal ICMP but still can not identify and classify syn-ack attack because syn-ack length packet have small value. IDS application also can not identify HTTP packet as a normal packet because http length packet value as same as TCP flooding length packet value. IDS log displayed as Web based so that can simplify user for analyzing attack paket.